THE EFFECT OF FINANCIAL ATTITUDE AND FINANCIAL KNOWLEDGE ON COMPANY PERFORMANCE WITH FINANCIAL DECISIONS AS INTERVENING VARIABLES: A BEHAVIORAL FINANCE PERSPECTIVE - Siti Aisyah Hidayati; Sri Wahyulina; Embun Suryani (Master of Management, Mataram University, 2021)
This study aims to analyze the effect of Financial Attitude and Financial Knowledge on Company Performance with Financial Decision as an Intervening Variable on Small and Middle Enterprises Owners in Lombok Island. This research's theoretical contribution is expected to contribute to the knowledge and development of behavioral finance theory related to Financial Decision-making and Company Performance in Small and Middle Enterprises. Besides, it is also hoped that behavioral finance will become a subject in the financial management course. Furthermore, this research's practical contribution is expected to provide input, suggestions, and recommendations to the NTB Provincial Government's policymakers in making policies related to SMEs' development. This research is research based on a quantitative approach, with this type of explanatory research. The study population was all SMEs in Lombok Island. The sampling was carried out by non-probability selection, namely using judgment sampling, selecting SMEs engaged in the pottery industry and had already exported. Of the existing population, there are 35 (Thirty-Five) SMEs that can be taken as samples. Respondents in this study are the owners of each of these SMEs. The data collection technique used in this study was to use a questionnaire. The data obtained will be processed as needed by using GSCA (Generalized Structured Component Analysis) statistical tools to achieve the research objectives and hypothesis testing. The results showed that Financial Attitude and Financial Knowledge had a positive and significant effect on Financial Decision-making. Financial Decisions did not mediate the impact of Financial Attitude and Financial Knowledge on Company Performance, and Financial Decisions had a negative and significant effect on Company Performance. This circumstance is also motivated by the age of most of the respondents of productive age, mostly male, most of the education level is high school, and the length of business is more than 10 (ten) years. Keywords: Financial Attitude, Financial Knowledge, Financial Decision, Company Performance